2012
DOI: 10.3329/ujzru.v30i0.10702
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diseases, morbidity and mortality of Black Bengal Goats under different management systems in Bangladesh

Abstract: Abstract:A study was carried out in Faridpur, Habiganj and Barisal to identify the prevalence of diseases, morbidity and mortality of Black Bengal goats (BBGs) under semi-intensive system reared by moderate and ultra poor households in Bangladesh during the period from February 2008 to July 2009. A total of 168 female goats and 9 bucks were recorded from two types of households of which 125 goats were infected (74.70%) by a number of diseases and lead to mortality (17.26%). Survival rates and mortality percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Small ruminants especially goat is very important in rural economy and has the potentially using as a tool for poverty reduction in Bangladesh [10]. It is considered as the poor man's cow [11] reared in backyard system by rural farmers, especially the poor women or children as an integral part of the farming system [12]. Different types of diseases both infectious and non-infectious are significant problems in goat rearing in our country.…”
Section: Introductionmentioning
confidence: 99%
“…Small ruminants especially goat is very important in rural economy and has the potentially using as a tool for poverty reduction in Bangladesh [10]. It is considered as the poor man's cow [11] reared in backyard system by rural farmers, especially the poor women or children as an integral part of the farming system [12]. Different types of diseases both infectious and non-infectious are significant problems in goat rearing in our country.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is frequently occurred at the rainy season compared to drier and colder season observed by Islam et al (2001) which is coincided with the survey period of this study. Kashem et al (2011) reported as highest percentage of adult mortality was due to PPR (38%) followed by pneumonia (24.14%) within the infections and other infectious causes such as diarrhea (13.8%) and contagious ecthyma (13.8%) found in adult goat. However, in the study area diarrhea was very common in both female (22.73%) and male (17.05%) whether it was continued with pneumonia (female 12.93% and male 18.97%); coccidiosis (female 11.63% and male 16.28%) those are similar with Noman et al (2011).…”
Section: Mortality Of Goat Kid Mortalitymentioning
confidence: 99%
“…However, in the study area diarrhea was very common in both female (22.73%) and male (17.05%) whether it was continued with pneumonia (female 12.93% and male 18.97%); coccidiosis (female 11.63% and male 16.28%) those are similar with Noman et al (2011). Furthermore, Noninfectious causes likely poisoning (female 62.5% and male 37.5%); accident (female 83.33% and male 16.67%) had lower effects on adult goat mortality which is also approved with Kashem et al (2011). Pregnant female were mostly died during difficulties in parturition.…”
Section: Mortality Of Goat Kid Mortalitymentioning
confidence: 99%
See 2 more Smart Citations